Fostering employability through mediation of protégé career self-efficacy of Pakistani bankers - Muhammad Shaukat Malik; Muhammad Kashif Nawaz (Cogent Business & Management, 2022)
Mentoring at its best is a life-altering relationship, and mentors play a pivotal role in protégé career upward progression. In a dynamic labor market, securing internal employability and also finding a better opportunity outside the organization that matched interests and skills are critical factors for individual career advancement. In line with this, the existing study probed to investigate the linkage between mentoring functions (traditional and relational) and protégé perceived employability (internal and external) through the mediation of protégé career self-efficacy. In line with this, the data were collected from 373 staff working in conventional and Islamic banks in Pakistan. Data were analyzed through PLS-SEM. The finding shows that mentoring functions (traditional and relational) were directly associated with protégé employability. Likewise, the results also indicate that protégé career self-efficacy mediates the proposed path. In the current study, both traditional and relational mentoring functions are investigated as the antecedent of career self-efficacy and perceived employability contributes to the existing literature.
Keywords: 650; career self-efficacy; perceived employability; relational mentoring functions; traditional mentoring functions